Circuits regulating pleasure and happiness: the evolution of reward-seeking and misery-fleeing behavioral mechanisms in vertebrates - Loonen, Anton J. M.; Ivanova, Svetlana A. (Frontiers in Neuroscience, 2015)
The very first free-moving animals in the oceans over 540 million years ago must have been able to obtain food, territory and shelter, as well as reproduce. Therefore, they would have needed regulatory mechanisms to induce movements enabling achievement of these prerequisites for survival. It can be useful to consider these mechanisms in primitive chordates, which represent our earliest ancestors, to develop hypotheses addressing how these essential parts of human behavior are regulated and relate to more sophisticated behavioral manifestations such as mood. An animal comparable to lampreys was the earliest known vertebrate with a modern forebrain consisting of old and new cortical parts. Lampreys have a separate dorsal pallium, the forerunner of the most recently developed part of the cerebral cortex. In addition, the lamprey extrapyramidal system, which regulates movement, is modern. However, in lampreys and their putative forerunners, the hagfishes, the striatum, which is the input part of this extrapyramidal system, probably corresponds to the human centromedial amygdala, which in higher vertebrates is part of a system mediating fear and anxiety. Both animals have well-developed nuclear habenulae, which are involved in several critical behaviors; in lampreys this system regulates the reward system that reinforces appetitive-seeking behavior or the avoidance system that reinforces flight behavior resulting from negative inputs. Lampreys also have a distinct glutamatergic nucleus, the so-called habenula-projection globus pallidus, which receives input from glutamatergic and GABAergic signals and gives output to the lateral habenula. Via this route, this nucleus influences midbrain monoaminergic nuclei and regulates the food acquisition system. These various structures involved in motor regulation in the lampreys may be conserved in humans and include two complementary mechanisms for reward reinforcement and avoidance behaviors. The first system is associated with experiencing pleasure and the second with happiness. The activities of these mechanisms are regulated by a tract running via the habenula to the upper brainstem. Identifying the human correlate of the lamprey habenula-projecting globus pallidus may help in elucidating the mechanism of the antidepressant effects of glutamatergic drugs.